O Diagrama V na experimentação em uma disciplina de Química Geral no ensino superior - Pereira, Raphael (2015)
The students graduating from High School, most of the time, come with deterministic versions of that is to doing Science, creating a distorted view of how to mere verification of what is laid from the experiental classes. They may have great difficulty to be free from non-reflective approach typical of the traditional school because of their previous experiences provided by uncritical methodologies with the presence of monologues. Institutionally, we also have a school that focuses on speech act by stimulus and not by reflection, which can interfere in the relations between thinking and doing of concern to obtain required score to pass the subject. This study aimed to analyze the use of V Diagram for students of Civil Engineering and Production Engineering in a discipline of General Chemistry in the construction of knowledge from experiments in the context of Higher Education in a private institution in the state of Espírito Santo. The methodology was characterized by a qualiquantitative approach from exploratory-descriptive goals combined, using as a procedural way to intervention-research developed in the field. There was an improvement in the development of experiments and communication students. The V Diagram can be used as a proposal for the organization of knowledge from the previous knowledge that the student brings his experience, not allowing the experimental classes are reported by mere uncritical records. The students said that even though complex construction V Diagram, preferred to build it when compared to traditional construction of the report. They also said that this methodology promotes interaction between thinking and doing in the construction of knowledge. still it could be said that there are similarities between theoretical aspects of the V Diagram and learning styles expressed by the Simon’s model (2010). However, when analyzing the values obtained in aspects of the V Diagram produced by students in the course of the ten experiments there was a significant relationship between their performances with their learning styles. The V Diagram is recommended in the construction of knowledge in the experimental classes of General Chemistry, as the results showed a significant improvement in the understanding of the experiments developed by the students.